Evaluation of Brazilian Sugarcane Bagasse Characterization: An Interlaboratory Comparison Study. (27th November 2019) - Sluiter, Justin B; Chum, Helena; Gomes, Absai C; Tavares, Renata P A; Azevedo, Vinicius; Pimenta, Maria T B; Rabelo, Sarita C; Marabezi, Karen; Curvelo, Antonio A S; Alves, Aparecido R; Garcia, Wokimar T; Carvalho, Walter; et al.
Abstract: This paper describes a study of the variability of measured composition for a single bulk sugarcane bagasse conducted across eight laboratories using similar analytical methods, with the purpose of determining the expected variation for compositional analysis performed by different laboratories. The results show good agreement of measured composition within a single laboratory, but greater variability when results are compared among laboratories. These interlaboratory variabilities do not seem to be associated with a specific method or technique or any single piece of instrumentation. The summary censored statistics provide mean values and pooled standard deviations as follows: total extractives 6.7% (0.6%), whole ash 1.5% (0.2%), glucan 42.3% (1.2%), xylan 22.3% (0.5%), total lignin 21.3% (0.4%), and total mass closure 99.4% (2.9%).